Dual-drugs delivery in Solid Lipid Nanoparticles for the treatment of Candida albicans mycosis - Carbone, C. (2020)
Supplementary material related to this article can be found, in the online version, at doi: https://doi.org/10.1016/j.colsurfb.2019.110705.